The impact of using superfood products on a sporty lifestyle - Długosz, Joanna; Staszczak, Paweł; Smuszkiewicz-Różański, Paweł; Różańska-Smuszkiewicz, Gabriela; Oronowicz, Radosław; Kmiotek, Weronika; Jaworska, Barbara; Ragan, Dagmara; Bara, Maciej; Miłkowski, Paweł (Quality in Sport, 2024)
The term "superfood" refers to foods that are exceptionally high in nutrients such as vitamins, minerals, antioxidants, and other bioactive substances, which have beneficial effects on health. Although there is no precise scientific definition, the term is widely used in the context of healthy eating and diets. Superfoods have a deep-rooted history dating back to ancient times, when foods like quinoa, chia seeds, goji berries, and turmeric were used for their health properties in various cultures around the world. For example, the Aztecs and Incas utilized quinoa and chia seeds as important dietary staples, valued for their nutritional content and ease of cultivation. In the 20th century, growing interest in healthy eating led to increased scientific research on the nutritional components of various food products. The term "superfood" began to be used to describe foods that provide specific health benefits, a concept that gained traction in health media and literature. Modern research confirms many beliefs about superfoods, emphasizing their ability to support physical and mental health. Superfoods like acai berries, chia seeds, and spirulina are popular among active individuals and athletes because they can aid muscle recovery, boost energy levels, and strengthen the immune system. Superfoods are integral to modern dietary trends such as the Mediterranean diet and veganism due to their potential health benefits. Thanks to their unique nutritional properties, they play a significant role in balanced diets and are widely used in everyday nutrition and complementary medicine to support the health and well-being of their consumers.